Algorithms to counter the pre-trial investigation of criminal offenses - D. A., Zhakudaev (Opción, 2019)
The purpose of this study is to determine the nature and main elements of the algorithm to counter a pre-trial investigation of criminal offenses. The leading methods of research of this problem were sociological methods of collecting information and methods of static observation and analysis. As a result, the determination of the dependence of resistance to the investigation is related to the ratio of factors of the volitional and motivational attitude of the person involved. In conclusion, the actual state of the measures aimed at preventing opposition to the investigation of criminal offenses.